Desaparecimento e morte de abelhas no brasil, registrados no aplicativo bee alert - Castilhos, Dayson (2018)
Two major problems in today beekeeping are the mass death and CCD (Colony Collapse Disorder) of bees, which are causing the world population decline of these species. In March 2014, an online survey was launched in order to assess the evolution of bee mass death and CCD events in Brazil. Colony losses happened from January 1st, 2013 to December 31st, 2016 were accepted to be posted in a web survey hosted in <http://www.nobeenofood. com/beealert>, as well as in apps. for smartphones and tablets, from interested collaborators to make their registrations. 247 qualified, confirmed and validated participants completed the questionnaires and were accepted to compose the BEE ALERT application database in that period. During visits to these apiaries, 38 dead honeybee samples were collected for analyses of pesticide residues by means of mass spectrometry (UHPLC-MS/MS). Statistical analysis showed that pesticides are reported as the main cause of mass deaths and CCD in the country. Total colony loss calculated for the period (2013-2016) was 52.2% with (95% CI 48.3-56.0%) and mean colony loss was 62.0% with (95% CI 57.9-66.1%). Neonicotinoids and fipronil lead pesticide lists (37.7%) and São Paulo state holds 47% of honeybee casualties in Brazil. Toxicological analyses showed multiple contamination with higher indices by fipronil with frequency of 68.4% and amplitude of (0.5-23.539,7 ng/g), thiamethoxam 42.1% and (0.6-13.6 ng/g), dinotefuran 42.1% and (0.6-205.0 ng/g), imidacloprid 28.9% and (2.4-16.2 ng/g), nitenpyram 5.3% and (3.8 -7.4 ng/g), acetamiprid 5.3% and (1.3-2.1 ng/g) and thiacloprid 2.6% (1.6 ng/g). Neonicotinoids and fipronil residues had higher frequencies and amplitude in honeybees collected near sugarcane plantations and orange orchards in northwest São Paulo and other agro industrial rural landscapes. Africanized honeybee (Apis mellifera) and the native bee jataí (Tetragonisca angustula) were the most harmed species. These systemic pesticides are the main mechanisms of mass death and disappearance of bees in Brazil, according to this research